2017
DOI: 10.1007/s10620-017-4583-1
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, Metabolic Syndrome, and Cardiovascular Risk in Gluten-Free Followers Without Celiac Disease in the United States: Results from the National Health and Nutrition Examination Survey 2009–2014

Abstract: Although being on a GFD may be beneficial in weight management, there was no significant difference in terms of prevalence of metabolic syndrome and CVD risk score in gluten-free followers without CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 38 publications
6
24
0
1
Order By: Relevance
“…In fact, large prospective cohort studies, including the National Health and Nutrition Examination Survey, have shown no risk of gluten contributing to cardiovascular disease or the metabolic syndrome. 4,5 Gluten ingestion may even improve health, as suggested by a series of prospective studies showing that gluten intake is inversely associated with the risk of developing type 2 diabetes, likely owing to the increased intake of cereal fiber with a gluten-containing diet. 6 Fourth, going gluten free may affect other aspects of diet and lifestyle.…”
mentioning
confidence: 99%
“…In fact, large prospective cohort studies, including the National Health and Nutrition Examination Survey, have shown no risk of gluten contributing to cardiovascular disease or the metabolic syndrome. 4,5 Gluten ingestion may even improve health, as suggested by a series of prospective studies showing that gluten intake is inversely associated with the risk of developing type 2 diabetes, likely owing to the increased intake of cereal fiber with a gluten-containing diet. 6 Fourth, going gluten free may affect other aspects of diet and lifestyle.…”
mentioning
confidence: 99%
“…In the current issue of Digestive Diseases and Sciences, Kim et al [6] provide the first report addressing the risk of metabolic syndrome and cardiovascular disease in individuals without celiac disease following a GFD compared to individuals consuming dietary gluten. Using large-scale database analysis gathered by the National Health and Nutrition Examination Survey (NHANES) 2009-2014, the authors report a 1.3% prevalence of non-celiac individuals following a GFD in the general population [6].…”
mentioning
confidence: 99%
“…Using large-scale database analysis gathered by the National Health and Nutrition Examination Survey (NHANES) 2009-2014, the authors report a 1.3% prevalence of non-celiac individuals following a GFD in the general population [6]. Non-celiac GFD followers in the general population had a significant decrease in weight over 1 year, lower waist circumference, and higher HDL cholesterol levels.…”
mentioning
confidence: 99%
See 2 more Smart Citations